Antibiotic Resistance Profile of Helicobacter Pylori Isolates from Dyspeptic Patients of Civil Hospital, Khairpur (Medical Forum Monthly, 2022)
Objective: To examine the frequency of H. pylori in patients with dyspepsia and also to test the antibiotic susceptibility profile of isolates.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Microbiology, Shah Abdul Latif University, Khairpur for one year from 01-Jan-2019 to 31-12-2019.Materials and Methods: Biopsy specimen from 100 patients with dyspepsia from both sexes was collected from civil hospital, Khairpur. After culturing the samples in Microbiology Institute, Shah Abdul Latif University, Khairpur, the identification of the samples was carried out (gram staining, catalase, oxidase and urease). The susceptibility profile to ten common antibiotics was tested by Disk diffusion method.Results: From total 100 subjects, 100 biopsy samples from were collected. Mean age of the patients in years were 40±15.4. Out of 100 biopsies, 30 were positive for H. pylori. From these positive samples, majority of 56.7% were isolated from males and 43.3% from females. Out of 30 isolates, 11.7% isolates were sensitive and 88.3% showed intermediate resistance. From 30 isolates, 4.7% isolates were sensitive to amoxicillin, 2.46% to metronidazole, 18.94% isolates to amikacin, 1.07% to novobiocin, 21.57% to ciprofloxacin, 31.88% isolates to levofloxacin, 31.88% to lincomycin and 22.90% isolates were sensitive to clarithromycin.Conclusion: The results showed that clarithromycin, levofloxacin, ciprofloxacin and moxifloxacin were sensitive while Amikacin and clavulanic acid/ amoxicillin showed intermediate resistance and novobiocin, amoxil and metronidazole, were resistant to H. pylori.